Sorafenib With and Without Transarterial Chemoembolization for Advanced Hepatocellular Carcinoma With Main Portal Vein Tumor Thrombosis: A Retrospective Analysis. (7th October 2015) - Zhang, Yingqiang; Fan, Wenzhe; Wang, Yu; Lu, Ligong; Fu, Sirui; Yang, Jianyong; Huang, Yonghui; Yao, Wang; Li, Jiaping
Abstract : Background: The survival benefit of combining sorafenib and transarterial chemoembolization (TACE) therapy compared with sorafenib monotherapy for patients with advanced hepatocellular carcinoma (HCC) and main portal vein tumor thrombosis (MPVTT) is unclear. Methods: Between January 2009 and June 2013, 183 consecutive patients with advanced HCC (Barcelona Clinic Liver Cancer stage C) and MPVTT were retrospectively reviewed. Of these, 89 patients with advanced HCC and MPVTT were enrolled in this study: 45 were treated with combination therapy (sorafenib‐TACE group), and the other 44 treated with sorafenib monotherapy (sorafenib group). Results: The mean number of TACE sessions per patient was 2.6 (range: 1–5). The median duration of sorafenib in the sorafenib‐TACE group and sorafenib group was 5.6 months and 5.4 months, respectively. The disease control rate was similar between the two groups. Median time to progression was 3.0 months (95% confidence interval [CI]: 2.2, 3.7) in the sorafenib‐TACE group, and 3.0 months (95% CI: 2.1, 3.8) in the sorafenib group ( p = .924). Median overall survival was 7.0 months (95% CI: 6.1, 7.8) and 6.0 months (95% CI: 4.7, 7.3) in the sorafenib‐TACE group and the sorafenib group, respectively ( p = .544). The adverse events related to sorafenib were comparable between the two groups. Twenty‐one adverse events of grade 3–4 related to TACE occurred in 12 patients (26.7%), and 2 of them died (4.4%). Conclusion: This study demonstrated no advantage of combination therapy over sorafenib monotherapy. Considering the patients' morbidity after TACE, sorafenib monotherapy is appropriate for managing patients with advanced HCC and MPVTT. Implications for Practice: For patients with advanced hepatocellular carcinoma (HCC) and main portal vein tumor thrombosis (MPVTT), no benefit was seen in this study in terms of disease control rate, time to progression, and overall survival for patients receiving sorafenib and transarterial chemoembolization compared with those receiving sorafenib monotherapy. Considering the patients' morbidity after combination therapy, monotherapy is appropriate for managing patients with advanced HCC and MPVTT. Abstract : The survival benefit of combining sorafenib and transarterial chemoembolization (TACE) therapy was compared with sorafenib monotherapy for patients with advanced hepatocellular carcinoma and main portal vein tumor thrombosis. Disease control rate, median time to progression, median overall survival, and occurrence of adverse events were similar between patients in the sorafenib‐TACE group and those treated with sorafenib monotherapy. Abstract : 摘要 背景 . 在晚期肝细胞癌(HCC)合并门静脉主干癌栓(MPVTT)患者中, 索拉非尼联合动脉化疗栓塞(TACE)治疗与索拉非尼单药相比的生存获益尚不明确。 方法 . 我们回顾了2009年1月至2013年6月期间的183例连续性晚期HCC(巴塞罗那临床肝癌分期C期)合并MPVTT患者的资料。研究纳入了其中89例晚期HCC合并MPVTT患者:45例接受了联合治疗(索拉非尼‐TACE组), 另外44例接受了索拉非尼单药治疗(索拉非尼组)。 结果 . 患者平均接受2.6次TACE(范围:1 ∼ 5)。索拉非尼‐TAEC组和索拉非尼组的中位索拉非尼治疗时间分别为5.6个月和5.4个月。两组的疾病控制率相似。索拉非尼‐TACE组的中位至疾病进展时间为3.0个月[95%置信区间(CI):2.2 ∼ 3.7], 索拉非尼组为3.0个月(95%CI:2.1 ∼ 3.8, P = 0.924)。索拉非尼‐TACE组和索拉非尼组的中位总生存分别为7.0个月(95%CI:6.1 ∼ 7.8)和6.0个月(95%CI:4.7 ∼ 7.3, P = 0.544)。两组的索拉非尼相关性不良事件发生率相似。12例患者(26.7%)发生了21宗3/4级TACE相关性不良事件, 其中2例患者死亡(4.4%)。 结论 . 本研究证实联合治疗与索拉非尼单药治疗相比没有优势。考虑到患者在接受TACE后的病损情况, 对于晚期HCC合并MPVTT患者采用索拉非尼单药治疗是适当的。 The Oncologist 2015;20:1417–1424 对临床实践的提示: 对于晚期肝细胞癌(HCC)合并门静脉主干癌栓(MPVTT)患者而言, 本研究未观察到索拉非尼联合动脉化疗栓塞与索拉非尼单药治疗相比在疾病控制率、至疾病进展时间和总生存方面的获益。考虑到晚期HCC合并MPVTT患者在接受联合治疗后的病损情况, 单药治疗是较为适当的选择。